A competitive protein interaction network buffers Oct4‐mediated differentiation to promote pluripotency in embryonic stem cells. Issue 1 (8th October 2013) - Muñoz Descalzo, Silvia; Rué, Pau; Faunes, Fernando; Hayward, Penelope; Jakt, Lars Martin; Balayo, Tina; Garcia‐Ojalvo, Jordi; Martinez Arias, Alfonso
Abstract : Pluripotency in embryonic stem cells is maintained through the activity of a small set of transcription factors centred around Oct4 and Nanog, which control the expression of 'self‐renewal' and 'differentiation' genes. Here, we combine single‐cell quantitative immunofluorescence microscopy and gene expression analysis, together with theoretical modelling, to investigate how the activity of those factors is regulated. We uncover a key role for post‐translational regulation in the maintenance of pluripotency, which complements the well‐established transcriptional regulatory layer. Specifically, we find that the activity of a network of protein complexes involving Nanog, Oct4, Tcf3, andβ ‐catenin suffices to account for the behavior of ES cells under different conditions. Our results suggest that the function of the network is to buffer the transcriptional activity of Oct4, which appears to be the main determinant to exit pluripotency. The protein network explains the mechanisms underlying the gain and loss of function in different mutants, and brings us closer to a full understanding of the molecular basis of pluripotency. Abstract : The dynamic competition for complex formation between the pluripotency network components Oct4, Nanog, Tcf3, and β‐catenin prevents embryonic stem cell differentiation by controlling the levels of free Oct4. Synopsis: The dynamic competition for complex formation between the pluripotency network components Oct4, Nanog, Tcf3, and β‐catenin prevents embryonic stem cell differentiation by controlling the levels of free Oct4. Pluripotency is defined by the ratios between the levels of pluripotency factors rather than by their absolute levels. Competition between different protein complexes involving Nanog, Oct4, Tcf3, and β‐catenin can account for the ratios associated with pluripotency. The unstable pluripotency of Nanog mutant cells was shown to depend on the interactions between Oct4 and β‐catenin. The function of the protein competition network is to control the levels of free Oct4, which are balanced by Nanog and β‐catenin in embryonic stem cells.